Genetic variability for grain yield and components in an early tropical yellow maize population under Striga hermonthica infestation - Badu-Apraku, Baffour; Menkir, A.; Lum, F. (Informa UK Limited, 2007)
A major problem that usually confronts the breeder is ensuring that there is sufficient genetic variability in a population for the trait being improved because this determines the breeding schemes to use for improvement and whether or not sufficient progress could be made. Three hundred full-sib families from cycle 3 of the early maturing yellow endosperm maize (Zea mays L.) population, TZE-Y Pop DT STR, were evaluated under artificial Striga hermonthica infestation at Mokwa and Abuja, Nigeria in 2003. The objectives of this study were to investigate the type of gene action involved in the inheritance of S. hermonthica resistance in TZE-Y Pop DT STR C3, determine the extent of genetic variability available in the population after three cycles of S1 recurrent selection, and the phenotypic and genetic correlation coefficients among the traits used for selecting for resistance to S. hermonthica. Estimates of dominance variances were larger than additive genetic variances for grain yield, plant height, ear height, number of ears at harvest, and Striga damage rating at 8 weeks after planting (WAP). Even though h2 estimates were generally low for most traits (< 0.40), moderate-to-large additive genetic variances, and wide ranges were obtained in TZE-Y Pop DT STR C3 for most traits, suggesting that there was adequate genetic variation for improving Striga resistance and grain yield in the population. Highly significant phenotypic correlation coefficients were obtained between grain yield and ears per plant, plant height, ear height, days to anthesis and silking, anthesissilking interval, and Striga damage score at 10 WAP. Recurrent selection methods that capitalize on both additive and dominance variances would be effective for improving the population for Striga resistance and grain yield.